Compota a base de Rollinia mucosa (anona) y Oenocarpus bataua Mart (ungurahui) y su valoración antioxidante - Padilla Tangoa, Richard (2022)
The objective of the research work was to obtain the technological parameters for the preparation of compote based on Rollinia mucosa (Anona) and Oenocarpus bataua (Ungurahui) and its antioxidant value. The research presents the quantitative approach of experimental type with randomized experimental design. To this end, the pulp (Myrciaria dubia), softening (Oenocarpus bataua) and peeling (Rollinia mucosa), heat treatment, packaging, sealing and storage were obtained. On the other hand, data processing and analysis consisted of analyzing the physicochemical, microbiological and sensory analysis properties of the compote. The results that were obtained according to the descriptive statistical analysis of the acceptability of the fruit-based compote sweetened with blonde and chancaca, the most accepted formulation was 926 with the following concentration Rollinia mucosa (50%), Oenocarpus bataua ( 50%) respectively, had a greater acceptance in all the attributes flavor, acidity, consistency and smell; According to the stability of the product, it will be extended that the product can be consumed in 7 months, demonstrating that the fruit-based compote is an acceptable product, has complementary properties and improves health care and thus can be an alternative to use of Amazonian raw materials in functional foods.